Answer:
-5
Explanation:
You can define the first integer to be x
The second integer would then be x + 1
The third integer would be (x + 1 ) + 1 which equals x + 2
The fourth integer would be (x + 2) + 1 which equals x + 3
Now set up your equation:
x + x + 1 + x + 2 + x + 3 = -18
4x + 6 = -18
4x = -24
x = -6 (This is your first integer)
To find the greatest, substitute the value for x into the four expressions to find the four integers:
First: x = -6
Second: x = -6 + 1 = -5
Third: x = -6 + 2 = -4
Fourth: x = -6 + 3 = -3
-5 is the greatest of these four values and is the answer.